Getting to know journal bibliographic databases. - Ng, K.H.; Peh, W.C.G. (2010)
A bibliographic database is an organised digital collection of references to published literature. A bibliographic database may be general in scope or may cover a specific academic discipline. There are many types of medical and general bibliographic databases. They cover biomedical and scientific literature, morbidity and mortality statistics, therapeutic regimens, medical records, images and reviews of evidence-based medicine. Getting to know these databases will help researchers and authors to enhance their writing and publishing endeavours.